Adaptive anti‐myocardial immune response following hospitalization for acute heart failure. (2nd May 2021) - Morbach, Caroline; Beyersdorf, Niklas; Kerkau, Thomas; Ramos, Gustavo; Sahiti, Floran; Albert, Judith; Jahns, Roland; Ertl, Georg; Angermann, Christiane E.; Frantz, Stefan; Hofmann, Ulrich; Störk, Stefan
Abstract: Aims: It has been hypothesized that cardiac decompensation accompanying acute heart failure (AHF) episodes generates a pro‐inflammatory environment boosting an adaptive immune response against myocardial antigens, thus contributing to progression of heart failure (HF) and poor prognosis. We assessed the prevalence of anti‐myocardial autoantibodies (AMyA) as biomarkers reflecting adaptive immune responses in patients admitted to the hospital for AHF, followed the change in AMyA titres for 6 months after discharge, and evaluated their prognostic utility. Methods and results: AMyA were determined in n  = 47 patients, median age 71 (quartiles 60; 80) years, 23 (49%) female, and 24 (51%) with HF with preserved ejection fraction, from blood collected at baseline (time point of hospitalization) and at 6 month follow‐up (visit F6). Patients were followed for 18 months (visit F18). The prevalence of AMyA increased from baseline ( n  = 21, 45%) to F6 ( n  = 36, 77%; P  < 0.001). At F6, the prevalence of AMyA was higher in patients with HF with preserved ejection fraction ( n  = 21, 88%) compared with patients with reduced ejection fraction ( n  = 14, 61%; P  = 0.036). During the subsequent 12 months after F6, that is up to F18, patients with newly developed AMyA at F6 had a higher risk for the combined endpoint of death or rehospitalization for HF (hazard ratio 4.79, 95% confidence interval 1.13–20.21; P  = 0.033) compared with patients with persistent or without AMyA at F6. Conclusions: Our results support the hypothesis that AHF may induce patterns of adaptive immune responses. More studies in larger populations and well‐defined patient subgroups are needed to further clarify the role of the adaptive immune system in HF progression.